The importance of comparative common law: A view from Singapore - PHANG, Andrew (Institutional Knowledge at Singapore Management University, 2023)
The central theme in the present article is that in developing its common law in a particular area, the courts in the jurisdiction concerned ought to have regard to developments in the corresponding area of law in other jurisdictions as well. The search (in the Singapore context) is one that traverses all relevant decisions in all relevant common law jurisdictions in order to glean the principles that are felt to be best suited not only from the perspective of logic, but also to Singapore society in general and the Singapore legal system in particular. Although this is the approach adopted by the Singapore courts, it is sufficiently general that it might serve as a possible model to be adopted—at least potentially—in other jurisdictions as well. It will be sought to illustrate this central theme by reference to some key decisions in the Singapore law of contract, its law of torts and its law of unjust enrichment.